A comparison of hydrogen permeation and the resulting corrosion enhancement of X65 and X80 pipeline steels. (January 2014) - Peng, X. Y.; Cheng, Y. F.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, corrosion and electrochemical hydrogen permeation behaviour of two grades of pipeline steel, X65 and X80 steels, were investigated by hydrogen-charging, electrochemical impedance spectroscopy measurements and metallographic observation. It was found that the corrosion and hydrogen permeation behaviour of steels is affected by their metallurgical features. Upon hydrogen-charging, both high grade of X80 pipeline steel and low grade of X65 steel show enhanced corrosion activity. The electrochemical hydrogen permeation current measurements and calculations show that the X80 steel contains a higher density of hydrogen traps than X65 steel, which may potentially result in the increased susceptibility of X80 steel to hydrogen-induced cracking (HIC). Dans ce travail, la corrosion électrochimique de l'hydrogène et un comportement de perméation de deux qualités d'acier de pipeline, X65 et X80 aciers, ont été étudiés par l'hydrogène charge, électrochimiquemesures de spectroscopie d'impédance et l'observation métallographique. On a constaté que lela corrosion et de l'hydrogène comportement de perméation des aciers est affectée par leurs caractéristiques métallurgiques.Sur hydrogène charge, à la fois de haute qualité en acier de pipeline X80 et X65 de bas grade de spectacle en acierune activité améliorée à la corrosion. L'hydrogène perméation électrochimique des mesures de courantet les calculs montrent que l'acier X80 contient une plus grande densité de pièges à hydrogène de X65acier, ce qui peut potentiellement entraîner l'augmentation de la sensibilité de l'acier X80 pour induite par l'hydrogène; Fissuration (HIC).